Strategi Pemasaran Travel Wisata Hasby Tour Desa Sumberbaru Kecamatan Sumberbaru Kabupaten Jember - Muhaimin, Muhammad Firman (Fakultas Dakwah UIN KHAS Jember, 2023)
Hasby Tour and Travel, as a travel agency committed to providing unforgettable travel experiences, adopts an innovative approach in its marketing strategy. The marketing strategy is guided by Hasby Tour and Travel’s policy, which sets a minimum quota for specific tour groups. Consequently, the agency not only caters to individual travel needs but also offers tailored opportunities for groups to enjoy customized offerings based on their participation scale. The purpose of this research is to understand the marketing strategy employed by Hasby Tour and Travel in the village of Sumberbaru, Sumberbaru District, Jember Regency. Additionally, the study aims to identify the supporting factors and obstacles in its implementation. The researcher utilized a qualitative descriptive research method. Research subjects were selected based on predefined criteria to enhance the research process’s success. Data collection techniques included interviews, observations, and documentation. Data validity was ensured through source triangulation. The study concludes that during the pandemic, Hasby Tour and Travel’s marketing strategy utilizes the STP approach (Segmentation, Targeting, Positioning). Furthermore, the SWOT analysis reveals the following: Strengths: Adherence to customer agreements regarding pricing and discounts. Weaknesses: Lack of physical office space and promotional efforts. Opportunities: Exploration of new locations and addressing minimal competition. Threats: Considerations related to organizational structure.